Identification of ciliary neurotrophic factor (CNTF) residues essential for leukemia inhibitory factor receptor binding and generation of CNTF receptor antagonists. - Di Marco, A (1996)
Ciliary neurotrophic factor (CNTF) drives the sequential assembly of a receptor complex containing the ligand-specific alpha-receptor subunit (CNTFR alpha) and the signal transducers gp130 and leukemia inhibitory factor receptor-beta (LIFR). The D1 structural motif, located at the beginning of the D-helix of human CNTF, contains two amino acid residues, F152 and K155, which are conserved among all cytokines that signal through LIFR. The functional importance of these residues was assessed by alanine mutagenesis. Substitution of either F152 or K155 with alanine was found to specifically inhibit cytokine interaction with LIFR without affecting binding to CNTFR alpha or gp130. The resulting variants behaved as partial agonists with varying degrees of residual bioactivity in different cell-based assays. Simultaneous alanine substitution of both F152 and K155 totally abolished biological activity. Combining these mutations with amino acid substitutions in the D-helix, which enhance binding affinity for the CNTFR alpha, gave rise to a potent competitive CNTF receptor antagonist. This protein constitutes a new tool for studies of CNTF function in normal physiology and disease.